A Systematic Review of the Seven Most Cultivated Mushrooms: Production Processes, Nutritional Value, Bioactive Properties and Impact on Non-Communicable Diseases - Maria Dimopoulou; Ioanna Chinou; Olga Gortzi (Agriculture)
Mushroom production, mushroom knowledge and mushroom cultivation have aroused the interest of many researchers, scientists, institutions, cultural and mushroom-loving associations, and ordinary mushroom pickers as well. The contribution of wild mushrooms to the economic, cultural and touristic development and social cohesion of the Greek rural population is considered very important. In addition to their therapeutic and dietary value, they are also valuable for their diverse chemical and medicinal properties. The PubMed—Medline, Web of Science and Cochrane Library databases were searched for relevant articles published up to January, 2025. Even today, some macromycetes are still used in medicine due to their remarkable healing properties. In the form of powders or solutions, they were formerly used as a remedy for epilepsy, tuberculosis, nervous diseases and various severe inflammations. This review documents the benefits of mushroom consumption suggested by health experts for pathological conditions and health improvement and highlights their superiority as non-animal protein sources according to their nutrients.